2021
DOI: 10.1159/000519487
|View full text |Cite
|
Sign up to set email alerts
|

The Regional Specificity of Mucosa-Associated Microbiota in Patients with Distal Colorectal Cancer

Abstract: <b><i>Background/Aims:</i></b> Recent studies have demonstrated that the populations of several microbes are significantly increased in fecal samples from patients with colorectal cancer (CRC), suggesting their involvement in the development of CRC. The aim of this study was to identify microbes which are increased in distal CRCs and to identify the specific location of microbes increased in mucosal tissue around the tumor. <b><i>Methods:</i></b> Tissue specimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…Most of the current studies on P. stomatis have used molecular techniques such as whole-genome sequenced and 16S rRNA gene ampli cation to directly analyze the composition of microbial species in mucosal tissues, feces and other related specimens from patients with oral and gastrointestinal in ammatory diseases and cancer [11]. It is found that there is a higher expression in patients with periodontitis [12], colorectal cancer, gastric cancer, oral cancer and gallbladder cancer, which is considered to be related to the pathogenesis of these diseases [13][14][15][16]. However, it is rare to isolate and culture P.stomatis and carry out routine identi cation and antimicrobial sensitivity test, there is no case report that it causes OAS.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the current studies on P. stomatis have used molecular techniques such as whole-genome sequenced and 16S rRNA gene ampli cation to directly analyze the composition of microbial species in mucosal tissues, feces and other related specimens from patients with oral and gastrointestinal in ammatory diseases and cancer [11]. It is found that there is a higher expression in patients with periodontitis [12], colorectal cancer, gastric cancer, oral cancer and gallbladder cancer, which is considered to be related to the pathogenesis of these diseases [13][14][15][16]. However, it is rare to isolate and culture P.stomatis and carry out routine identi cation and antimicrobial sensitivity test, there is no case report that it causes OAS.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Fn abundance is substantially higher in the tumor than in neighboring normal mucosal tissue from the same individual ( Castellarin et al., 2012 ; Kostic et al., 2012 ; Flanagan et al., 2014 ; Li et al., 2016 ; Gao et al., 2017 ; Yamaoka et al., 2018 ). Interestingly, in the surrounding tissue of CRC, the abundance of Fn is gradually decreased with the distance from the tumor ( Cuellar-Gómez et al., 2021 ; Kono et al., 2021 ). Fn is also positively associated with the progress of CRC.…”
Section: Temporal and Spatial Distribution Of Fn In Crcmentioning
confidence: 99%